FABRICATION AND CHARACTERIZATION OF THE COMPOSITES OF RESIN - HUSK OF RICE AND RESIN - RUB ASH - Muhammad Lawrence Pattersons; Arin Naripa; Sendiko Janu Winarno; Siti Mawaddah Abhan; Edi Sanjaya (Program Studi Fisika Universitas Negeri Jakarta, 2018)
We have done the fabrication of two kinds of composite material the fillers that we used rub ash for one type of composite and the husk of rice for another, the matrix for both is resin. The resin - rub ash composite, the volume ratio of filler and matrix is 1:1, while in the resin - husk of rice composite we used three volume ratios, those are 1:1, 1:2, and 2:1. After the process of fabrication was done, we did TGA test and three points flexural test for every composite we fabricated. The results of TGA test show that the most significant weight decrease of resin - rub ash composite occurred at 390,29 ÂºC, while the resin - rub ash composite's most considerable weight decrease occurred at 399,86 ÂºC. The results of three points flexural test show that elasticity of resin - rub ash composite is 4,97 x 109 N/m2, while elasticity modulus of all kinds of the resin - husk of rice composite is in order of 108 N.m2 and 106 N/m2. Overall, we can conclude that the resin - husk of rice composite is more heatproof and more elastic than the resin - rub ash composite.